Data Tracking Analysis of the Geomagnetic Fixed-Station Network in China - Suqin Zhang; Changhua Fu; Xiuxia Zhang; Yi Zhang (Data Science Journal, 2018)
Data tracking analysis is an important mechanism for increasing data analysis capacity and eliminating interference from observational data. In this study, the technique was applied to the geomagnetic fixed-station network to improve the efficiency and accuracy of analysis to extract useful information. This paper introduces the scope, workflow, analysis platform, abnormal variation status, and results of the geomagnetic data tracking analysis. We present some typical examples of abnormal variations in addition to our proposals for future work.